2014
DOI: 10.1007/s10072-014-1666-z
|View full text |Cite
|
Sign up to set email alerts
|

Neurofunctional correlates of attention rehabilitation in Parkinson’s disease: an explorative study

Abstract: The effectiveness of cognitive rehabilitation (CR) in Parkinson's disease (PD) is in its relative infancy, and nowadays there is insufficient information to support evidence-based clinical protocols. This study is aimed at testing a validated therapeutic strategy characterized by intensive computer-based attention-training program tailored to attention deficits. We further investigated the presence of synaptic plasticity by means of functional magnetic resonance imaging (fMRI). Using a randomized controlled st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
72
0
8

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(82 citation statements)
references
References 15 publications
2
72
0
8
Order By: Relevance
“…One low‐quality, exploratory study evaluated cognitive rehabilitation for improving cognitive impairment in PD patients receiving computer‐based cognitive training; some significant effects were reported. Because of the exploratory character of the study and the small sample size, the efficacy conclusion is “ insufficient evidence .” Because of the limited data available for MCI in PD, the practice implication is “ investigational .” Because of the lack of safety data, there is “ insufficient evidence ” to conclude on the safety of cognitive rehabilitation for cognitive impairment in PD.…”
Section: Results and Conclusionmentioning
confidence: 99%
“…One low‐quality, exploratory study evaluated cognitive rehabilitation for improving cognitive impairment in PD patients receiving computer‐based cognitive training; some significant effects were reported. Because of the exploratory character of the study and the small sample size, the efficacy conclusion is “ insufficient evidence .” Because of the limited data available for MCI in PD, the practice implication is “ investigational .” Because of the lack of safety data, there is “ insufficient evidence ” to conclude on the safety of cognitive rehabilitation for cognitive impairment in PD.…”
Section: Results and Conclusionmentioning
confidence: 99%
“…Identification of processing speed deficits is particularly important since this construct has the potential to be modified with cognitive training [4046]. Edwards et al [41] demonstrated that PD subjects could improve cognitive processing speed over a three-month period through a self-administered task using speed of processing training (SOPT) software (InSight).…”
Section: Discussionmentioning
confidence: 99%
“…Cognitive rehabilitation programmes in PD have demonstrated their efficacy in improving a wide range of cognitive domains . Previous PD studies have also shown functional brain changes after cognitive rehabilitation in the short term . Recently, in a previous study from our group, patients with PD, after attending a 3‐month cognitive rehabilitation programme, demonstrated improvements in cognition and functional disability , which were accompanied by increased brain functional connectivity (FC) and activation .…”
Section: Introductionmentioning
confidence: 99%